A model of health promotion service in breast cancer by community pharmacist in Bangkok / รูปแบบการให้บริการสร้างเสริมสุขภาพในโรคมะเร็งเต้านมของเภสัชกรชุมชน เขตกรุงเทพมหานคร - Saiyalam, Chanawit; Sitthiworanan, Chanthonrat (Naresuan University Journal: Science and Technology (NUJST); Vol 23 No 2 (2015): May-August 2015, 2015)
การวิจัยนี้มีจุดประสงค์เพื่อสารวจความรู้ ทัศนคติ เนื้อหา กิจกรรมและอุปสรรคของเภสัชกรชุมชน เขตกรุงเทพมหานครที่นาไปสู่การพัฒนารูปแบบการให้บริการสร้างเสริมสุขภาพในโรคมะเร็งเต้านม โดยมีการดาเนินงาน 3 ขั้นตอน คือ 1) การสารวจการให้บริการสร้างเสริมสุขภาพในโรคมะเร็งเต้านมของเภสัชกรชุมชน เขตกรุงเทพมหานคร โดยใช้แบบสอบถาม ผลการวิจัย พบว่าร้อยละของคะแนนความรู้ ทัศนคติ และอุปสรรคการสร้างเสริมสุขภาพในโรคมะเร็งเต้านมของเภสัชกรชุมชน คือ 67.5, 85.8 และ 70.6 ตามลาดับ เภสัชกรชุมชนส่วนใหญ่ให้ความสาคัญ และระบุถึงความสามารถที่ทาได้ในส่วนของเนื้อหาและกิจกรรมการสร้างเสริมสุขภาพในโรคมะเร็งเต้านมในร้านยา แต่ไม่เคยทากิจกรรมมาก่อนหน้านี้ 2) การสร้างและพัฒนารูปแบบการให้บริการสร้างเสริมสุขภาพด้วย 6 เครื่องมือ ได้แก่ คู่มือการปฏิบัติงาน แบบประเมินปัจจัยเสี่ยงโรคมะเร็งเต้านม อุปกรณ์ให้ความรู้กับผู้มารับบริการในรูปแบบของแผ่นพับ แผ่นพลิก โปสเตอร์ และป้ายประชาสัมพันธ์หน้าร้านแบบ X– stand 3) การนารูปแบบจากขั้นตอนที่ 2 ไปทดลองใช้จริงใน 3 ร้านยาที่ถูกคัดเลือก ครั้งที่ 1 ระยะเวลา 10 วัน และนามาปรับปรุงเพื่อนาไปใช้อีกในครั้งที่ 2 ระยะเวลา 20 วัน ร้อยละของคะแนนความพึงพอใจ ในครั้งที่ 1 และ ครั้งที่ 2 ของผู้มารับบริการ เท่ากับ 81.8 และ 90.8 ของเภสัชกรผู้ให้บริการ เท่ากับ 92.9 และ 85 ตามลาดับ โดยสรุป การให้บริการสร้างเสริมสุขภาพโรคมะเร็งเต้านมมีประโยชน์สาหรับผู้รับบริการและสามารถนาไปใช้ได้ในร้านยา ทั้งนี้อุปสรรคที่พบ ได้แก่ เวลาที่จากัดของผู้รับบริการ และความไม่เพียงพอของจานวนเภสัชกรในการให้บริการ ดังนั้นการนาไปใช้ในอนาคต ควรปรับปรุงในด้านเนื้อหาของเครื่องมือที่ใช้ให้สั้น เข้าใจง่ายและใช้เวลาที่รวดเร็ว คำสำคัญ: รูปแบบ มะเร็งเต้านม การสร้างเสริมสุขภาพ ร้านยา เภสัชกรชุมชน This research aimed to explore knowledge, attitude, content, activities and obstacles of community pharmacists in Bangkok, leading to develop a model regarding health promotion service in breast cancer. This study was divided into three stages. 1) Exploring breast cancer health promotion service through questionnaires. The results demonstrated percentage of community pharmacists’ knowledge, attitude and obstacles in breast cancer health promotion were 67.5, 85.8 and 70.6, respectively. Most community pharmacists paid attention to the services and had capabilities to perform activities in drugstores; however, they have never implemented in drugstores. 2) Establishing and developing six tools of the breast cancer health promotion service model as practice manuals, breast cancer risk assessment form, educational materials including pamphlets, flipcharts and posters, and outdoor X– stand banners for service advertising. 3) Applying the service model from the second stage to three drugstores for use in the 1st period of ten days, then enhanced and further used for the 2nd period of twenty days. The study presented percentage of satisfaction in breast cancer health promotion service in the 1st and 2nd period by customers were 81.8 and 90.8, and by pharmacists were 92.9 and 85, respectively. In summary, the model of health promotion service of breast cancer seems benefit to customers and can be apply for uses in drugstores. However, possible obstacles may be found such as no time of customers for attending and less number of pharmacists for service providing. Therefore, the model of health promotion service in breast cancer in the future shall be improved in brief content and easy understanding of health education materials, and short duration for service providing. Keywords: Model, Breast Cancer, Health promotion, Drugstore, Community Pharmacist
Keywords: รูปแบบ มะเร็งเต้านม การสร้างเสริมสุขภาพ ร้านยา เภสัชกรชุมชน Model, Breast Cancer, Health promotion, Drugstore, Community Pharmacist